Some questions on the law on the state of emergency - Chochova, Maria (Law Journal of New Bulgarian University, 2021)
The article analyses two provisions of the Law on Measures and Actions in the State of Emergency, declared with the decision of the National Assembly of 13th March 2020, providing for suspension and extension of time periods provided in the legislation. The analysis is focused on examples based on the review of the labour legislation. The issue of suspended court proceedings on some labour disputes – until the end of the state of emergency – is also discussed.